2017
DOI: 10.1111/mec.14159
|View full text |Cite
|
Sign up to set email alerts
|

High gene flow despite opposite chirality in hybrid zones between enantiomorphic door snails

Abstract: We studied differentiation and geneflow patterns between enantiomorphic door-snail species in two hybrid zones in the Bucegi Mountains (Romania) to investigate the effects of intrinsic barriers (complications in copulation) and extrinsic selection by environmental factors. A mitochondrial gene tree confirmed the historical separation of the examined populations into the dextral Alopia livida and the sinistral Alopia straminicollis in accordance with the morphological classification, but also indicated gene flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…However, Nordsieck (, ) supposed that the two taxa hybridize only to a limited extent. In contrast, the admixture analyses of the nuclear markers (Figure ; see Koch et al, for additional analyses) showed that most specimens in the hybrid zones have a combination of similarly large components from the genomes of the parental taxa irrespective of their classification (Figure ; Koch et al, ). The introgression between the two taxa in the hybrid zones resulted in a fusion of their populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Nordsieck (, ) supposed that the two taxa hybridize only to a limited extent. In contrast, the admixture analyses of the nuclear markers (Figure ; see Koch et al, for additional analyses) showed that most specimens in the hybrid zones have a combination of similarly large components from the genomes of the parental taxa irrespective of their classification (Figure ; Koch et al, ). The introgression between the two taxa in the hybrid zones resulted in a fusion of their populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the gene flow estimates between A. livida nubila and A. straminicollis monacha and between A. livida hypula and A. s. straminicollis are higher than those between the taxa within the A. livida complex (Figure ). There is also frequent introgression of mitochondrial haplotypes (Figure ; Koch et al, ). The hybrid zones between A. livida and A. straminicollis in the Tatar Gorge and the Velican Valley were known based on morphological evidence (Nordsieck, ; Szekeres, , 2008, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clausiliids are high‐spired snails, which typically copulate by shell mounting. This type of copulation may not so severely restrict mating between the wild type and left–right reversed variant as face to face copulation in flat/globular stylommatophorans (Asami, Cowie, & Ohbayashi, ; Gittenberger, ; Koch, Neiber, Walther, & Hausdorf, ; Ueshima & Asami, ; Utsuno, Kasem, Fukuda, & Asami, ). Evolution of left–right reversed taxa has been more frequent in high‐spired pulmonate groups than in low‐spired groups, probably because of relaxation of positive frequency‐dependent selection against reversal in the former resulting from their possible interchiral copulation success (Asami et al., ; Gittenberger, ).…”
Section: Discussionmentioning
confidence: 99%